Trends in nanomaterial-based biosensors for viral detection. Issue 2 (1st June 2022) - Harito, Christian; Khalil, Munawar; Septiani, Ni Luh Wulan; Dewi, Kariana Kusuma; Hardiansyah, Andri; Yuliarto, Brian; Walsh, Frank C
Abstract: Pandemics such as COVID-19 have highlighted the importance of point-of-care sensors for testing, tracing, and treatment to minimize and manage infection. Biosensors have been widely deployed in portable devices such as glucose sensors and pregnancy tests. Their development for point-of-exposure virus detection or point-of-care devices is anticipated but their reliability for the accurate detection of viruses is critical. Nanomaterials, such as metal nanoparticles (NPs), magnetic NPs, quantum dots, carbon-based nanomaterials, and molecularly imprinted polymer (MIP) NPs, have been utilized in biosensors to enhance sensitivity. Molecular imprinting is a cost-effective method to synthesize polymers for selective binding, which have excellent properties as biosensors. More research on MIP NPs can be expected in the near future. The utilization of nanomaterials in several types of transducers for biosensor devices is also illustrated to give an overview of their use. Finally, a summary is given together with a future perspective on how biosensors can be further developed as reliable, portable viral biosensors.